2020
DOI: 10.1186/s13550-020-00730-1
|View full text |Cite
|
Sign up to set email alerts
|

The value of 18F-PSMA-1007 PET/CT in identifying non-metastatic high-risk prostate cancer

Abstract: Background Clinical management decisions on prostate cancer (PCa) are often based on a determination of risk. 68Ga-prostate-specific membrane antigen (PSMA)-11-positron emission tomography (PET)/computer tomography (CT) is an attractive modality to assess biochemical recurrence of PCa, detect metastatic disease and stage of primary PCa, making it a promising strategy for risk stratification. However, due to some limitation of 68Ga-PSMA-11 the development of alternative tracers is of high interest. In this stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
47
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(51 citation statements)
references
References 24 publications
4
47
0
Order By: Relevance
“…Further, a higher primary tumour SUVmax was confirmed in the high-risk group compared to the intermediate-risk group. Two smaller [ 18 F]PSMA-1007 studies [ 33 , 34 ] and a similar [ 68 Ga]Ga-PSMA-11 study [ 35 ] have shown a similar correlation with higher SUVmax of the primary prostate tumour with increasing PSA levels and Gleason score/ISUP grade. In cases when a prostate biopsy cannot be performed due to patient preference or contraindications, the SUVmax of the primary tumour on the [ 18 F]PSMA-1007 PET/CT may be indirectly used to estimate ISUP grade with higher SUVmax values implying a likelihood of a high ISUP grade.…”
Section: Discussionmentioning
confidence: 83%
“…Further, a higher primary tumour SUVmax was confirmed in the high-risk group compared to the intermediate-risk group. Two smaller [ 18 F]PSMA-1007 studies [ 33 , 34 ] and a similar [ 68 Ga]Ga-PSMA-11 study [ 35 ] have shown a similar correlation with higher SUVmax of the primary prostate tumour with increasing PSA levels and Gleason score/ISUP grade. In cases when a prostate biopsy cannot be performed due to patient preference or contraindications, the SUVmax of the primary tumour on the [ 18 F]PSMA-1007 PET/CT may be indirectly used to estimate ISUP grade with higher SUVmax values implying a likelihood of a high ISUP grade.…”
Section: Discussionmentioning
confidence: 83%
“…The differentiation between 68 Ga-PSMA positive and negative scans was not statistically significant (mean PSA: 8.39 ± 23 vs. 4.22 ± 5.99 ng/mL, median PSA: 2.71 vs. 1.40 ng/mL, n.s.). The detection efficacy in the patient group Ga-RP was 75% (12) for PSA levels of 0.2 to <0.5 ng/mL, 86.7% (13), 76.9% (10), 94.4% (17), and 88.9% (24) for PSA levels of 0.5 to <1, 1 to < 2, 2 to < 5, and ≥5 ng/mL, respectively (p = 0.108) (Table 6). All of the 28 BCR patients in the F-RT patient group showed a positive 18 F-PSMA scan (100%) (mean PSA 9.10 ± 10.16 ng/mL) with 15 patients with PSA levels of 2 to <5 ng/mL and 13 patients with PSA values of ≥5 ng/mL, respectively.…”
Section: Positivity Rate With [ 68 Ga]ga-psma-11 Pet/ct In Patients W...mentioning
confidence: 98%
“…Further, a higher primary tumour SUVmax was con rmed in the high-risk group compared to the intermediate-risk group. Two smaller [ 18 F]PSMA-1007 studies [22,23] and a similar [ 68 Ga]Ga-PSMA-11 study [24] have shown a similar correlation with higher SUVmax of the primary prostate tumour with increasing PSA levels and Gleason score/ISUP grade. In cases when a prostate biopsy cannot be performed due to patient preference or contraindications, the SUVmax of the primary tumour on the [ 18 F]PSMA-1007 PET/CT may be indirectly used to estimate ISUP grade with higher SUVmax values implying a likelihood of a high ISUP grade.…”
Section: Discussionmentioning
confidence: 80%